Indigenising framing knowledge from content-analysing the weblog frames built on chedet.com - Chang, Peng Kee; Fauziah Ahmad,; Wan Amizah Wan Mahmud, (2010)
Framing is believed to be the universally applied research approach in the field of communication science nowadays (Bryant & Miron, 2004). The process of framing in communication can be examined from the outlook of frame-building and frame-setting by the media professionals (de Vreese, 2005). Many studies have been conducted in scrutinising the news frames for the comprehension of frame-building exercises by media organisations. The authors have ascertained that news sources play an important role in promoting predominant frames (Chang et al, 2009). Tun Dr. Mahathir Mohamad, who was once the country premier, turns into a policy critic and is actively expressing his opinions through blogging on chedet.com since May 2008. It is believed that the source’s predominant frames were also portrayed by him through the online social interactive media. An empirical examination on the weblog contents with five generic-frame measurements developed by Semetko & Valkenburg (2000) was able to explain the phenomena in blogosphere. The visibilities of frames were compared by the two different languages used together with the targeted person and organisations being highlighted on this weblog from May to December 2008. The results showed both language and target had impacts on the visibility of frames. Meanwhile, the effect size of target was found greater than language in explaining the variances.